2008
DOI: 10.1176/appi.ajp.2008.07111774
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of Aggression and Violence

Abstract: Acts of violence account for an estimated 1.43 million deaths worldwide annually. While violence can occur in many contexts, individual acts of aggression account for the majority of instances. In some individuals, repetitive acts of aggression are grounded in an underlying neurobiological susceptibility that is just beginning to be understood. The failure of "top-down" control systems in the prefrontal cortex to modulate aggressive acts that are triggered by anger provoking stimuli appears to play an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
619
0
42

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 795 publications
(711 citation statements)
references
References 261 publications
24
619
0
42
Order By: Relevance
“…Witnessing violence perpetrated by others may lead youth to model such behaviors through a social learning process (Bandura, 1977;Widom, 1989). CU traits are relevant to this process in that these youth may be at even greater risk for engaging in violence given that they are also prone to deficits in empathy (Frick, 2006;Frick, Barry, & Bodin, 2000), are less affected by the negative consequences of their aggressive behavior, such as the victim's distress (Pardini, Lochman, & Frick, 2003), and are less emotionally engaged by or physiologically responsive to such cues (Blair, 1999;Kimonis et al, 2006;2008).…”
Section: Exposure To Violence Mediates the Link Between Cu Traits Andmentioning
confidence: 99%
“…Witnessing violence perpetrated by others may lead youth to model such behaviors through a social learning process (Bandura, 1977;Widom, 1989). CU traits are relevant to this process in that these youth may be at even greater risk for engaging in violence given that they are also prone to deficits in empathy (Frick, 2006;Frick, Barry, & Bodin, 2000), are less affected by the negative consequences of their aggressive behavior, such as the victim's distress (Pardini, Lochman, & Frick, 2003), and are less emotionally engaged by or physiologically responsive to such cues (Blair, 1999;Kimonis et al, 2006;2008).…”
Section: Exposure To Violence Mediates the Link Between Cu Traits Andmentioning
confidence: 99%
“…4 Neurobiologically, impulsive/affective aggression may be explained as a lack of equilibrium between prefrontal mechanisms of top-down control (orbitofrontal cortex and anterior gyrus cinguli) and the bottom-up limbic stimuli (amygdala and other limbic areas), in which several neurotransmitters, such as serotonin, dopamine, noradrenalin and others, may be involved and may, therefore, be managed pharmacologically. 5,6 Several studies have demonstrated that aggression is a result of the combination of socioenvironmental, psychological and biological factors, and that an environment favorable to personal development may modulate unfavorable genetic characteristics. 7,8 However, biological factors of aggressive behaviors may and should be carefully managed because of probable mid-and long-term impairments and the progression into severe psychiatric disorders in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…In humans and nonhuman primates, aggressive behavior operates within social hierarchies to facilitate resource acquisition (3). Among the neurochemicals implicated in aggression (4,5), arginine vasopressin (AVP), and its homolog vasotocin, have been found to regulate several forms of aggression in numerous species (6, 7) across diverse taxa (8,9). Even in humans, central AVP correlates with aggressive behavior (10) and mediates anger (11).…”
mentioning
confidence: 99%